An advanced electrocatalyst for efficient synthesis of ammonia based on chemically coupled NiS@MoS2 heterostructured nanospheres. Issue 10 (21st April 2021) - Huang, Shoushuang; Gao, Chunyan; Xin, Peijun; Wang, Haitao; Liu, Xiao; Wu, Ye; He, Qingquan; Jiang, Yong; Hu, Zhangjun; Chen, Zhiwen
Abstract : Here, uniform NiS@MoS2 core–shell microspheres were controllably prepared by the in situ growth of MoS2 nanosheets on the nanoplates of NiS2 –NiS hierarchical microspheres, and they exhibited efficient catalytic activity for ambient NRR reaction. Abstract : The electrochemical reduction of nitrogen, as a sustainable alternative to the known Haber–Bosch process, possesses promising application prospects in the development of renewable energy storage systems. However, the yield of NH3 and Faraday efficiency are usually very low owing to the loss of active electrocatalysts and competitive hydrogen evolution reactions. Herein, uniform NiS@MoS2 core–shell microspheres are controllably prepared as a potential catalyst for an ambient electrocatalytic N2 reduction reaction. The NiS@MoS2 microspheres possess highly active intrinsic, sufficient accessible active sites, high structural porosity, and convenient transport channels, consequently boosting the transmission of electrons and mass. Additionally, the interfacial interaction between NiS and MoS2 facilitates electron transfer, which further improves the catalytic activity by optimizing the free energies of reaction intermediates. As a result, the titled NiS@MoS2 shows excellent electrochemical activity and selectivity, capable of achieving a relatively high NH3 yield of 9.66 μg h −1 mgcat −1 at −0.3 V ( vs. the reversible hydrogen electrode, RHE) and a high FE of 14.8% at −0.1 V vs. RHE in 0.1 M Na2 SO4 . The work demonstrated here may open a new avenue for the rational design and synthesis of catalysts for the electrochemical synthesis of ammonia.